Multigramme synthesis and asymmetric dihydroxylation of a 4-fluorobut-2E-enoate - Laurenson, James A. B.; Parkinson, John A.; Percy, Jonathan M.; Rinaudo, Giuseppe; Roig, Ricard (Beilstein Journal of Organic Chemistry, 2013)
Esters of crotonic acid were brominated on a multigramme scale using a free radical procedure. A phase transfer catalysed fluorination transformed these species to the 4-fluorobut-2E-enoates reproducibly and at scale (48–53%, ca. 300 mmol). Asymmetric dihydroxylation reactions were then used to transform the butenoate, ultimately into all four diastereoisomers of a versatile fluorinated C4 building block at high enantiomeric-enrichment. The (DHQ)2AQN and (DHQD)2AQN ligands described by Sharpless were the most effective. The development and optimisation of a new and facile method for the determination of ee is also described; 19F{1H} spectra recorded in d-chloroform/diisopropyl tartrate showed distinct baseline separated signals for different enantiomers.
Keywords: asymmetric; dihydroxylation; ee determination; fluorination; fluorosugars; organo-fluorine

(untitled) - Tsuchiya, T. (Adv. Carbohydr. Chem. Biochem., 1990)

(untitled) - Hartman, M. C. T.; Jiang, S.; Rush, J. S.; Waechter, C. J.; Coward, J. K. (Biochemistry, 2007)

(untitled) - Compain, P.; Martin, O. R. (Curr. Top. Med. Chem., 2003)

(untitled) - Murray, B. W.; Wittmann, V.; Burkart, M. D.; Hung, S.-C.; Wong, C.-H. (Biochemistry, 1997)

(untitled) - Withers, S. G.; MacLennan, D. J.; Street, I. P. (Carbohydr. Res., 1986)

(untitled) - Sianidis, G.; Wohlert, S.-E.; Pozidis, C.; Karamanou, S.; Luzhetskyy, A.; Vente, A.; Economou, A. (J. Biotechnol., 2006)

(untitled) - Burkart, M. D.; Vincent, S. P.; Düffels, A.; Murray, B. W.; Ley, S. V.; Wong, C.-H. (Bioorg. Med. Chem., 2000)

(untitled) - Schengrund, C.-L.; Kováč, P. (Carbohydr. Res., 1999)

(untitled) - Ichikawa, Y.; Lin, Y. C.; Dumas, D. P.; Shen, G. J.; Garcia-Junceda, E.; Williams, M. A.; Bayer, R.; Ketcham, C.; Walker, L. E. (J. Am. Chem. Soc., 1992)

(untitled) - Errey, J. C.; Mann, M. C.; Fairhurst, S. A.; Hill, L.; McNeil, M. R.; Naismith, J. H.; Percy, J. M.; Whitfield, C.; Field, R. A. (Org. Biomol. Chem., 2009)

(untitled) - Dax, K. (Sci. Synth., 2006)

(untitled) - Nieschalk, J.; O'Hagan, D. (J. Fluorine Chem., 1998)

(untitled) - Caravano, A.; Field, R. A.; Percy, J. M.; Rinaudo, G.; Roig, R.; Singh, K. (Org. Biomol. Chem., 2009)

(untitled) - Guha, S. K.; Shibayama, A.; Abe, D.; Sakaguchi, M.; Ukaji, Y.; Inomata, K. (Bull. Chem. Soc. Jpn., 2004)

(untitled) - Li, Q.; Wang, W.; Berst, K. B.; Claiborne, A.; Hasvold, L.; Raye, K.; Tufano, M.; Nilius, A.; Shen, L. L.; Flamm, R.; Alder, J.; Marsh, K.; et al. (Bioorg. Med. Chem. Lett., 1998)

(untitled) - Purrington, S. T.; Woodard, D. L.; Cale, N. C. (J. Fluorine Chem., 1990)

(untitled) - Durrant, G.; Green, R. H.; Lambeth, P. F.; Lester, M. G.; Taylor, N. R. (J. Chem. Soc., Perkin Trans. 1, 1983)

(untitled) - Gershon, H.; Shanks, L.; Gawiak, D. E. (J. Med. Chem., 1976)

(untitled) - Percy, J. M.; Roig, R.; Singh, K. (Eur. J. Org. Chem., 2009)

(untitled) - Kim, D. W.; Jeong, H.-J.; Lim, S. T.; Sohn, M.-H. (Angew. Chem., Int. Ed., 2008)

(untitled) - Fan, R.-H.; Zhou, Y.-G.; Zhang, W.-X.; Hou, X.-L.; Dai, L.-X. (J. Org. Chem., 2004)

(untitled) - Kolb, H. C.; VanNieuwenhze, M. S.; Sharpless, K. B. (Chem. Rev., 1994)

(untitled) - Walsh, P. J.; Sharpless, K. B. (Synlett, 1993)

(untitled) - Blundell, P.; Ganguly, A. K.; Girijavallabhan, V. M. (Synlett, 1994)

(untitled) - Körber, K.; Risch, P.; Brückner, R. (Synlett, 2005)

(untitled) - Morikawa, K.; Park, J.; Andersson, P. G.; Hashiyama, T.; Sharpless, K. B. (J. Am. Chem. Soc., 1993)

(untitled) - Becker, H.; Sharpless, K. B. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Gupta, A. K.; Kazlauskas, R. J. (Tetrahedron: Asymmetry, 1992)

(untitled) - Chi, Y.; Peelen, T. J.; Gellman, S. H. (Org. Lett., 2005)

(untitled) - Bergmann, H.; Grosch, B.; Sitterberg, S.; Bach, T. (J. Org. Chem., 2004)

(untitled) - Enders, D.; Thomas, C. R.; Runsink, J. (Tetrahedron: Asymmetry, 1999)

(untitled) - Bailey, D. J.; O'Hagan, D.; Tavasli, M. (Tetrahedron: Asymmetry, 1997)

(untitled) - Parker, D. (Chem. Rev., 1991)

(untitled) - Pirkle, W. H. (J. Am. Chem. Soc., 1966)

(untitled) - Tavasli, M.; Courtieu, J.; Goss, R. J. M.; Meddour, A.; O'Hagan, D. (Chem. Commun., 2002)

(untitled) - Gao, Y.; Sharpless, K. B. (J. Am. Chem. Soc., 1988)

(untitled) - Xiong, C.; Wang, W.; Hruby, V. J. (J. Org. Chem., 2002)

(untitled) - Byun, H.-S.; He, L.; Bittman, R. (Tetrahedron, 2000)

(untitled) - Guo, H.; O'Doherty, G. A. (J. Org. Chem., 2008)

(untitled) - Gerard, B.; Sangji, S.; O'Leary, D. J.; Porco, J. A., Jr (J. Am. Chem. Soc., 2006)

(untitled) - Jones, G. B.; Wright, J. M.; Rush, T. M.; Plourde, G. W., II; Kelton, T. F.; Mathews, J. E.; Huber, R. S.; Davidson, J. P. (J. Org. Chem., 1997)